Tiger Woods, Nike, and I are (Not) Best Friends: How Brand’s Sports Sponsorship in Social-Media Impacts Brand Consumer’s Congruity and Relationship Quality - Do, H.; Ko, E.; Woodside, Arch (Routledge, 2015)
This study examines the effects of brand’s sports sponsorship in social media on brand consumer’s congruity and brand relationship quality. The study included a survey of targeting consumers whose ages range between early twenties and late forties; data from 322 respondents were collected. The results are as follows. First, brand’s sports sponsorship in social-media activities relating to sports brands has significant effects on brand consumer’s congruity. Second, this congruity significantly influences brand relationship quality. Third, male consumers, who have previously purchased products and services associated with a sports brand, perceive the sponsor’s brand image more positively when they are exposed to the sponsor’s brand’s sports sponsorship in social-media activities, compared to those consumers having no previous purchases of the sponsored brand. Lastly, consumers in their forties with prior experience consuming the sponsor’s brand products are most affected by the level of selfcongruity with the sports brand compared to younger or older consumers.